2020
DOI: 10.1182/blood-2020-136422
|View full text |Cite
|
Sign up to set email alerts
|

SWOG S1826: A Phase III, Randomized Study of Nivolumab Plus AVD or Brentuximab Vedotin Plus AVD in Patients with Newly Diagnosed Advanced Stage Classical Hodgkin Lymphoma

Abstract: Although most patients (pts) with newly diagnosed stage III or IV Hodgkin lymphoma (HL) will be cured with initial therapy (tx), about 20-25% of pts will have relapsed or refractory (R/R) HL. The standard initial tx for adults with advanced stage HL, doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD), is associated with pulmonary toxicity due to bleomycin. Recent studies have demonstrated that in pts with a negative interim PET scan, the omission of bleomycin after 2 cycles is non-inferior with regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 0 publications
0
42
0
2
Order By: Relevance
“…In April 2022, six phase 3 trials (five in HL patients) are further defining the role of brentuximab vedotin. The SWOG S1826 (NCT03907488) trial is comparing the already mentioned BV-AVD regimen against the AVD combined with an anti-PD1 Ab nivolumab (N-AVD) instead of the ADC in both pediatric and adult patients with newly diagnosed advanced stage HL [ 80 ]. The AHOD1331 trial (NCT02166463) is comparing a scheme with brentuximab vedotin, doxorubicin, vincristine sulfate, etoposide, prednisone, and cyclophosphamide (BV-AVEPC) vs. doxorubicin, bleomycin, vincristine, etoposide, prednisone, and cyclophosphamide (ABVE-PC) in children and young adults with stage IIB or stage IIIB-IVB HL.…”
Section: Target Clinical Efficacy and Side Effects Of Available Adcsmentioning
confidence: 99%
“…In April 2022, six phase 3 trials (five in HL patients) are further defining the role of brentuximab vedotin. The SWOG S1826 (NCT03907488) trial is comparing the already mentioned BV-AVD regimen against the AVD combined with an anti-PD1 Ab nivolumab (N-AVD) instead of the ADC in both pediatric and adult patients with newly diagnosed advanced stage HL [ 80 ]. The AHOD1331 trial (NCT02166463) is comparing a scheme with brentuximab vedotin, doxorubicin, vincristine sulfate, etoposide, prednisone, and cyclophosphamide (BV-AVEPC) vs. doxorubicin, bleomycin, vincristine, etoposide, prednisone, and cyclophosphamide (ABVE-PC) in children and young adults with stage IIB or stage IIIB-IVB HL.…”
Section: Target Clinical Efficacy and Side Effects Of Available Adcsmentioning
confidence: 99%
“…Secondly, for first-line treatment of advanced cHL, further data are required to determine the optimal brentuximab vedotin combination regimen. An ongoing phase III study comparing A + AVD versus nivolumab plus AVD in patients with advanced cHL will assess the value of first-line brentuximab vedotin and immune checkpoint inhibitor combination therapy [71].…”
Section: Ongoing Controversies For Anti-cd30 Therapy In Chlmentioning
confidence: 99%
“…A recent example is the Southwest Oncology Group (SWOG) S1826 trial (NCT03907488) which randomized patients to receive either brentuximab vedotin (Adcetris; Seattle Genetics, Takeda), doxorubicin, vinblastine and dacarbazine (A + AVD) or Nivolumab plus AVD in patients with Hodgkin lymphoma. 10 This is concerning considering that doxorubicin, bleomycin, vinblastine and dacarbazine (ABVD) remains the standard of care, as the ECHELON-1 study has to date only shown a modest improvement in progression-free survival (PFS) for A + AVD vs. ABVD. 11 Claims of OS improvement must be tempered by the use of brentuximab as a post protocol therapy among patients on the control arm.…”
Section: Industry-sponsored Studies Prioritize the Patientmentioning
confidence: 99%